2013
DOI: 10.1109/jphot.2013.2285726
|View full text |Cite
|
Sign up to set email alerts
|

2-$\mu\hbox{m}$ Tm-Doped All-Fiber Pulse Laser With Active Mode-Locking and Relaxation Oscillation Modulating

Abstract: We report on the actively mode-locked and relaxation-oscillation-modulated 2-m all-fiber laser, using an electronic optical phase modulator with fiber pigtail. Linear-cavity and ring-cavity fiber lasers with Tm-doped fiber were set up with a center wavelength around 1.95 m. Actively mode-locked stable pulse train was generated with a repetition rate of 11.884 MHz (linear cavity) and 12.099 MHz (ring cavity), and the duration of the pulse was 816 ps and 446 ps, respectively. The stable pulse train with a durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…When the function generator works around the relaxation oscillation of the fiber laser, this fiber laser can also generate stable pulse train [14][15][16]. For example, by turning the frequency of the FG to 27.778 kHz, the pulse train shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the function generator works around the relaxation oscillation of the fiber laser, this fiber laser can also generate stable pulse train [14][15][16]. For example, by turning the frequency of the FG to 27.778 kHz, the pulse train shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…In this experiment, the difference from the mode-locking regime mentioned above is that the pump power would definitively affect the shape of the pulse train. This is because of the connection between the pulse train and the relaxation oscillation phase of the fiber laser [16].…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Because the water vapor and some important greenhouse gas molecules in the atmosphere exhibit characteristic absorption lines around 2 μm wavelength region [1][2], TDFLs can be used in a wide range of applications, such as noninvasive surgery, remote sensing, laser radar, free-space telecommunications [3][4][5][6], etc. Many theoretical and experimental studies on TDFLs have been reported [7][8][9][10][11][12][13][14][15][16][17][18]. However, most of previously reported research mainly concentrated in high power [7][8][9][10][11] or pulse lasing [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Wang Xiong et al published an active mode-locked thulium-doped fiber laser with an all-fiber structure, whose repetition frequency mode-locked pulse laser can reach 11.884 MHz and 12.099 MHz. [15] Kneis et al reported an active mode-locked thulium-doped fiber laser with high average power and tunable wavelength in 2015. [16] In 2016, Wang et al reported an active mode-locked thulium-doped fiber laser using pump modulation.…”
mentioning
confidence: 99%